Drooling in children with neurodisability: A survey of Australian speech–language pathologists' practice. (2nd September 2020) - McInerney, Michelle; Reddihough, Dinah S; Carding, Paul N; Imms, Christine
Abstract: Purpose: In the absence of evidence-based guidelines, this study sought to understand current speech-language pathologists' (SLPs) practice when treating drooling in children with a neurodisability. Method: Descriptive research using cross-sectional survey methodology. Online survey methods were used to obtain specific information on Australian SLPs' self-reported assessment and treatment practices relative to working with children with neurodisability who drool. Questions focussed on level of expertise, treatment approaches and barriers to evidence-based practice (EBP) in this area. Participants were sourced through three targeted associations/organisations. Data were analysed using descriptive and non-parametric statistics. Result: Participants were Australian SLPs who had recent experience working with children with neurodisability who drool ( n = 68). They favoured informal rather than formal methods for assessment. Preferred treatment techniques included behavioural intervention methods (46–53%) and modifying positioning (43.3%). Client suitability dominated reasoning regarding treatment selection (60%) with 57% of SLPs reporting EBP barriers. Conclusion: Drooling was perceived to be a complex practice area for which SLPs desire additional education. Despite availability, valid and reliable assessments of drooling were not commonly used. Clinicians have limited evidence to support their practice: further research is needed to establish evidence-based treatments for drooling.